'European Elections are Second‐Order Elections': Is Received Wisdom Changing?. (5th August 2014) - Corbett, Richard
Abstract Is it still right to classify European elections as 'second‐order elections'? There are some reasons used to justify such a classification that are changing or evolving, while others are not. A neat and tidy first‐/second‐order division may not be appropriate. But is the 'lead candidate' (Spitzenkandidat) development one of the reasons to re‐evaluate? In most Member States, it had little impact on the election campaign and, at the time of writing, the effect on the final choice of Commission President is not definitively settled, but it looks as though it has changed the expectations of many politicians involved in that choice. Its longer term evolution remains to be seen and could well become more important for political actors, but the jury is still out as to how far this might eventually impact on the wider public.